Valoración económica del servicio de secuestro de CO2 en un bosque de colina baja, distrito de Punchana, Loreto, 2022 - Freire del Castillo, Maria Yessenia (2023)
The economic value of the CO2 sequestration service was quantified in a low hill forest in the district of Punchana, Loreto, Peru. Data from the forest census of the commercial species of the low-hill forest of the private property of J.R. Aguirre was evaluated. A total of 14 commercial forest species, nine botanical families and 69 trees were recorded. The Myristicaceae family shows a highest number of species. The results show that the economic value of CO2 sequestration is USD 3458,12/ha. The species with the highest contribution are Vochysia vismiifolia (USD 391,34/ha), Eschweilera bracteosa (USD 385,27/ha) and Ecclinusa lanceolata (USD 296,43/ha). A significant statistical difference (? = 0,05) in the average of economic value of CO2 between species was found.